Speed skills of players selected for Lower Silesian Regional Teams - Świerzko, Kamil; Rokita, Andrzej; Klimczak, Katarzyna (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Team sports require comprehensive motor preparation of players. In addition to strength and endurance skills, increasing attention is being given to the development of players’ speed skills. Aim of Study. The aim of the study was to evaluate reaction time and 30-metre, straight line sprint time in players selected for the Lower Silesian Regional Teams in Poland in 2013 and 2014. Material and Methods. The study involved 369 players aged 13–15 years (187 girls and 182 boys), members of football, handball, volleyball and basketball Regional Teams of Lower Silesia. Out of this group, 51 players participated in the study in 2013, and then repeated it in 2014. The study used Smart Jump and Smart Speed Systems to measure players’ reaction and sprint times, which were measured at 5, 10, 15, 20, 25 and 30-metre intervals. Results. Mean reaction time to light stimuli observed in boys in 2013 and 2014 was 0.509 ± 0.141 and 0.467 ± 0.264 seconds, respectively. In girls, the mean reaction time was 0.553 ± 0.122 and 0.566 ± 0.0271 seconds in 2013 and 2014, respectively. Mean sprint time in 2013 for boys who were not selected for the Regional Teams the following year was 5.338 ± 0.285 seconds, while those who were selected reached 5.416 ± 0.321 seconds. Girls who did not qualify for the Regional Teams in 2014 achieved the time of 5.764 ± 0.305 seconds. The female players who repeated the study reached the mean time of 5.805 ± 0.28 seconds. Boys who joined the Regional Teams in 2014 had a 30-metre sprint time of 5.533 ± 0.359 s. Boys who were repeating the study achieved the time of 5.322 ± 0.295 s. Girls who were selected for the Regional Teams in 2014 reached 5.796 ± 0.348 s, while girls who were repeating the study – 5.839 ± 0.342 s. Conclusions. The players’ reaction times may suggest that this ability was not a criterion for selecting male and female players for the Regional Teams of Lower Silesia. Male handball players were shown to posses the greatest speed potential
Keywords: speed; team sports; choice and selection; reaction time; 30-metre sprint time